Research on Aesthetics of Cross-Cultural Creative Product Design - Hu , Jiamin; Sayuti , Nurul’ Ayn Binti Ahmad; Qingfeng , Liu (Journal of Posthumanism, 2025)
Cross-cultural creative product design takes globalization as the background, regional culture as the core, creativity as the driving force to considers the needs and differences of consumers with different cultural backgrounds to carry out cross-cultural communication and dissemination. Design aesthetics plays an irreplaceable role in improving the aesthetic value dimension of cultural creative products, which mobilizes consumers’ emotions and value judgment from a deeper level.However, in the study of cross-cultural cultural creative product design, many designers focus on the methods of different cultural’ s integration, but ignore the importance of product aesthetic value. This paper use methodology of literature review and case study to introduce the related concepts of design aesthetics and cross-cultural creative product design, and explores the concept of cross-cultural creative product design from the perspective of aesthetics design. Results from artistic aesthetics; regional aesthetics, functional aesthetics and commercial aesthetics are four aspects to analyze the characteristics of cross-cultural creative product design from the perspective of design aesthetics. The purpose of this study is to provide some new design theory references for cultural creative product design researchers, and internationalize the excellent traditional culture to promote cultural exchange and dissemination.